Developing Reading Fluency: Insights into the Effective Fluency Instruction - Bouguebs, Radia (Journal of Human Sciences, 2019)
Reading fluency allows the reader to focus his cognitive attention on gaining meaning from what is read. Because of its strong impact on comprehension, researchers and educators’ interest is centered on testing the best conditional practices that would sustain the development of reading fluency and provide an indirect support to reading comprehension. On one hand, this descriptive exploratory study digs deep on the existing literature on the functional relationship between reading fluency and comprehension; and on the other hand, it sheds light on the different direct fluency instructions proved effective since Samuels’ repeated reading (1979) to the most recent ones: fluency integrated instructional routines. As the effect of the combined fluency instructional strategies is higher than the effect of a fluency instruction working individually, we recommend the Fluency Oriented Reading Instruction as the most effective literacy program for EFL learners